Diphtheria Outbreak among Children in 2017–2018: a Single Centre Study in Indonesia - Aliza, Nur; Maemun, Siti; Yoenoes, Dedet Hidayati; Syafendra, Mega Oktariena; Amin, Desrinawati Muhammad; Afrina, Yeni; Rahmawani, Atika; Aryanto, Dara Tyas Putri; Murtiani, Farida (Global Medical & Health Communication (GMHC), 2023)
Diphtheria is an acute infectious disease caused by the bacterium Corynebacterium diphtheriae. Accurate and prompt diagnosis is essential for effective case management, predicting disease prognosis, preventing complications, and ensuring cost-effective medical intervention. This study aimed to assess the variety of clinical symptoms exhibited by pediatric diphtheria cases during an outbreak. An observational cross-sectional study was conducted using data from the medical records of pediatric diphtheria cases at Sulianti Saroso Infectious Disease Hospital from November 1, 2017, to February 28, 2018. The study involved 202 cases, and statistical analysis was performed using the chi-square test. Out of the 202 cases, 58.4% were male. Age distribution was <1 year: 7.4%, 1–2 years: 3.5%, >2–5 years: 24.8%, >5–12 years: 45.5%, and >12 years: 18.8%. Anamnestic findings revealed the presence of fever in 88.1% of patients, pain upon swallowing in 73.3%, and cough in 55.4%. Clinically, every patient exhibited pseudomembrane formations. Other findings included bilateral tonsillar involvement in 53%, lymphadenopathy in 40.1%, bullneck in 17.8%, and snoring in 7.9%. Four significant variables were associated with the diphtheria diagnosis: fever, snoring, bullneck, and snoring (p<0.05) respectively. Clinical signs and symptoms are pivotal in establishing a diphtheria diagnosis in pediatric cases.